The Clinical Evidence-Based Paradigm of Topical Anti-Aging Skincare Formulations Enriched with Bio-Active Peptide SAI-III (KPI) as Collagen Modulator: From Bench to Bedside - Rovero, Paolo; Malgapo, Dennis Malvin Hernandez; Sparavigna, Adele; Beilin, Ghislaine; Wong, Vincent; Lao, Ma Purita (Clinical, cosmetic and investigational dermatology, 2022)
A substantial reduction in the amount and quality of collagen leads to age-related deterioration of the elasticity and firmness of the skin. In recent years, multiple compounds have been developed aimed at reversing the molecular features of dermal aging. One such target for aging reversal is collagen degradation or turnover. SAI-III is a decapeptide (Ac-Met-Gly-Lys-Val-Val-Asn-Pro-Thr-Gln-Lys-N[H.sub.2]), also known as KPI, formally derived from the C-terminal portion of serpin A1, an agent known as a physiological inhibitor of neutrophil elastase, and has been the subject of laboratory and clinical studies determining its effects on modulation of collagen turnover as well as the treatment of age-associated changes of the face. This review aims to provide a bioinspired approach focusing on the latest scientific studies that describe the compound, as well as a comprehensive appraisal of laboratory and clinical tests on skincare formulations enriched with sA1-III. Keywords: KPI, prejuvenation, aging skin, aging well, anti-aging, SAI-III